Gambaran berat badan dan kadar HBA1C pada tikus wistar (Rattus norvegicus) model diabetes melitus tipe 2 yang diinduksi streptozotocin dan sukrosa - Saha, Daniel Setyawan; Agnes Frethernety; Ni Nyoman Sri Yuliani (Barigas: Jurnal Riset Mahasiswa, 2023)
The incidence of people with diabetes mellitus (DM) continues to increase over time. The World Health Organization (WHO) predicts a substantial increase in the number of people with Type 2 diabetes mellitus in the coming years. Patients with diabetes mellitus should be able to control their weight and blood glucose levels to reduce the risk of complications by performing glycemic control examinations such as HbA1c examination and managing a healthier lifestyle and regular exercise. The method used is true experimental design with the design used in this study is pre-posttest control group design to see the average weight and HbA1c levels of wistar rats before and after treatment. This study was divided into 2 research groups consisting of Normal group (KN), rats without streptozotocin induction and treatment group (KP), rats induced by streptozotocin that have met the inclusion and exclusion criteria. The conclusion of this study is that there is an increase in body weight and HbA1c levels in mice induced streptozotocin.